Ixazomib in addition to chemotherapy for the treatment of acute lymphoblastic leukemia in older adults. Issue 6 (12th May 2022) - Amrein, Philip; Ballen, Karen; Stevenson, Kristen; Brunner, Andrew; Hobbs, Gabriela; Hock, Hanno; McAfee, Steven; Moran, Jenna; Bergeron, Meghan; Foster, Julia; Bertoli, Christina; McGreggor, Kristin; et al.
Abstract: We sought to assess the safety of adding ixazomib, an oral proteasome inhibitor, to a multi-agent treatment regimen for older adults with acute lymphoblastic leukemia (ALL). Patients 51 to 75 years of age with newly diagnosed ALL were screened. Induction consisted of prednisone (P), vincristine (V), and doxorubicin (D). For BCR-ABL1+ patients, dasatinib was added. On Days 1, 8, 15 of induction, ixazomib was given orally. After induction patients received 1 cycle of consolidation in which ixazomib was given on Days 1, 8, 15. After consolidation, patients in remission (CR) were offered stem cell transplantation. Among the 19 patients treated, 15 (79%) [90% CI, 58–92%] achieved CR or CRi. At 2 years, the overall survival was 47% [95%CI, 29–72%]. In this study the dose of 2.3 mg of ixazomib in combination was the MTD for older patients with ALL and is the recommended dose for future phase 2 studies.